Dinamika ikhtilaf ulama dalam Islam kajian metodologis terhadap perbedaan pendapat dalam istinbath hukum - Fadillah Julya Putri; Muhammad Suma Hafiz; Nurul Azwa; Siti Khoriah Fitriani; Saipuddin Yuliar (Jurnal Pendidikan Agama Islam, 2026)
Differences of opinion among Muslim scholars constitute a natural phenomenon within the Islamic intellectual tradition and are inseparable from the dynamics of ijtihad in interpreting the primary sources of Islamic teachings. This article aims to analyze the underlying causes of scholarly disagreement (ikhtilaf) and to explain the methodological and contextual factors that contribute to its emergence. This study employs a qualitative approach through library research by examining classical and contemporary literature related to usul al-fiqh and the development of Islamic legal schools. The findings indicate that differences of opinion arise from varying interpretations of the Qur’an and Hadith, differences in assessing the authenticity and transmission of narrations, diverse methods of legal reasoning (istinbath), variations in the application of principles of usul al-fiqh, as well as the influence of social and cultural contexts surrounding the scholars. Therefore, such differences should not be viewed as contradictions, but rather as reflections of the flexibility of Islamic law and the richness of its intellectual heritage, which call for a wise and tolerant attitude in responding to them.